GERENCIAMENTO DA OPERAÇÃO E MANUTENÇÃO EM EMPREENDIMENTOS CERTIFICADOS AMBIENTALMENTE: DESAFIOS E OPORTUNIDADES - Brito, Douglas Malheiro de; Azevedo, Alberto; Costa, Dayana Bastos; Ferreira, Emerson A. M. (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The facilities management phase of a construction project has great importance in relation to its life cycle, especially in terms of overall costs. Sustainable projects with environmental certification are designed to achieve levels of performance during use, resulting in water and energy consumption reduction, however, several factors that occur during the design, construction and operation phases can influence the non-achievement of the performance predicted. The aim of this study is to identify the main challenges and opportunities in the facilities phase to continuity in compliance with the performance requirements of certified projects. An investigation was held, consisting of interviews with two certified facilities managers and technical visits in projects, focusing on checking the achievement of planned reductions in water and energy consumption, and relevant aspects of possible deviations. The results indicate non-achievement of the proposed performance in the certification phase, and the main challenges and opportunities experienced. The main study contribution is the better understanding of the important aspects, which can support the process of new project conception, planning and certification.